Competitiveness Issues in the Cultural Sector in Puglia Region During Covid-19 Times – Empirical Evidence of Nett Project (UNWE Yearbook, 2022)
The article aims to analyze some empirical evidence for competitiveness in the cultural sector in the Puglia region during COVID-19 times. In particular, the results of NeTT project, part of the Interreg VA Greece-Italy 2014 – 2020 program, are analyzed. Fourteen cultural operators from various spheres of the cultural life of the region were interviewed and five key dimensions of COVID-19 influence were studied, namely: digital, educational, media, regional and community. These areas are subject to a border evaluation from the regional authorities. The study confirms the research thesis that the COVID-19 pandemic situation can be used as an accelerator for competitiveness in the cultural sector in the Puglia region, and as a key for new sociological, educational, and behavioral patterns and joint artistic interven.